The Influence Of Human Resource Managementstrategies On Nurse Performance In RSU Bunda Thamrin Medan - Yansnita Mendrofa; Deli Theo; Ramadhani Syafitri Nasution (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
The study purpose was to analyze the influence of human resource management (HRM) strategies on nurse performance at Bunda Thamrin General Hospital in Medan. As nurses play a critical role in healthcare delivery, their performance is essential for service quality and patient satisfaction. This study specifically examined the impact of recruitment and selection, training and development, and organizational commitment on the work performance of nurses. The research was conducted in response to ongoing challenges in staff absenteeism, complaints from patients, and underperformance despite structured HR policies. Materials and methods. The study employed a quantitative approach using a cross-sectional survey design. A total of 70 nurses were selected through stratified random sampling from different hospital units. Data were collected using a structured questionnaire and analyzed using IBM SPSS Statistics version 26. Descriptive statistics were used to describe participant demographics, while Pearson correlation and multiple linear regression analyses were employed to examine the relationship between HRM variables and nurse performance. Ethical approval was obtained, and participation was voluntary and confidential. Results. The findings revealed a positive and statistically significant correlation between HRM strategies and nurse performance. Among the HRM components, training and development had the highest influence (r = 0.684, p < 0.01), followed by organizational commitment and recruitment. Regression analysis indicated that HRM strategies accounted for 54.8% of the variance in nurse performance (Adjusted R² = 0.548). Conclusions. Human resource management strategies, particularly training, recruitment, and organizational commitment, significantly affect nurse performance. Hospitals should strengthen these strategies to improve service delivery and staff productivity.